Sharia Banking Financing: Can It Increase The Output of Micro Small and Medium Enterprises in Indonesia? - Luspita, Dini; Novitasari, Rina; Rustami, Dea; Nopiah, Ririn (Journal of Islamic Economics and Philanthropy, 2025)
The trend of increasing bank interest rates means that MSMEs cannot pay off their debts to the bank, and ultimately, the bank will confiscate their property to pay off their debts. For this reason, the community and micro and small-scale business actors need a financing system that supports business success, namely a profit-sharing system. Sharia banking, a financial institution with operational principles based on Islamic Sharia, can carry out this type of transaction. Sharia banking has basic principles prohibiting interest (riba) and applying a profit-loss sharing system in every financing transaction. This research aims to see the influence of Sharia banking financing on MSMEs in Indonesia. The method used in this research is multiple linear regression analysis. Based on the results of this research, Sharia banking financing seen from Mudharabah, Musyarakah, Murabahah, Ujrah and Istishna has a significant influence on MSMEs